Development at the World Trade Organization - Rolland, Sonia E. (Oxford, 2012)
With the Doha Round on the rocks, the tension between the WTO's trade liberalization agenda and the development needs of many member states is more pronounced than ever. This book looks at the position of developing countries at the WTO from an institutionalist perspective and presents a range of proposals for change.